HARMONISASI PENGATURAN TENTANG KEWENANGAN DALAM PENERBITAN SURAT PERSETUJUAN BERLAYAR (SPB) KAPAL IKAN DI PELABUHAN BELAWAN DITINJAU DARI UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN DAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Sitompul, Muhammad Said (JURNAL MERCATORIA, 2016)
Harmonization of regulations on competence (authority) in the Issuance Agreement Fish Sailing Ships in the Port of Belawan in terms of the Act.No. 17 of 2008 with the Act.No. 45 of 2009, particularly the provisions of Article 42 of Law. No. 45 of 2009 related to the authority of the harbor master in the issuance of the Letter of Approval Sailing, that disharmony (disharmony) legislation between Law. 17 of 2008 by Law.No. 45 of 2009, as well as including the rules below. Furthermore, the (legitimate) Letter of Approval issued by the harbor master Sailing Fishing in the port of Belawan, are legal under the law. No. 45 of 2009, but contrary to the Act. No. 12 Year 2011 on the Establishment of legislation is contrary to the principles of the law of the formation of law (the principle of legal drafting). Syahbandar legal responsibility in the fishing port was not entirely responsible for the accident because the fishing boats in the laws have not been set, but the laws of the cruise itself clearly and in detail to explain matters of ship wrecks including the inspection procedure shipwrecks.